PENGARUH HARGA DIRI TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA DI BANJARMASIN - Sulistia Fahrunnisa Imani; Lita Ariani (Fakultas Psikologi Universitas Wijaya Putra, 2023)
This research aims to determine the influence of self-esteem on consumer behavior among students in Banjarmasin. The population in this study were students in the city of Banjarmasin. Data were collected using two scales, namely, the 31-item Consumer Behavior Scale (α= 0.955) and the 21-item Self-Esteem Scale (α= 0.918). The research subjects were students in Banjarmasin with a total of 200 subjects and the sample was determined using non-probability sampling using purposive sampling. Based on data analysis in this research through statistical testing using the Pearson product moment correlation technique, it can be concluded that there is a positive and significant influence between self-esteem and consumer behavior in students. The results of this research are that there is a significant influence between self-esteem and consumer behavior. The coefficient of determination (R square) is 0.281 with a value (Sig.) of 0.000, meaning that there is an influence between the influence of self-esteem on consumer behavior of 28%, which means 72% is influenced by other factors.